The Role of Green Intellectual Capital and Busy Director as Moderators of the Influence of Prudence and Audit Tenure on Integrated Reports - Whittleliang Hakki, Tandry; Akwila, Karvicha; Jurjanta, Priccilya (DINASTI RESEARCH, 2024)
Financial reports are financial information of a company in an accounting period that can be used to describe the performance of a company (Kashmir in Gayatri). Financial reports are said to be good if they have integrity over the information contained therein. Along with the convergence of IFRS, the concept of conservatism is now replaced by prudence, what is meant by prudence in IFRS is that revenue recognition may be recognized even though it is still potential, as long as it meets the provisions for revenue recognition but still uses the principle of prudence in its recognition. After SAK adopted IFRS. This study aims to test the effect of Prudence, Audit Tenure on the Integrated Report and examine whether there is a role of Green Intellectual Capital and Busy Director as a moderation of the influence of Prudence, Audit Tenure on the Integrated Report carried out by the company. This study took the research population from financial sector companies listed on the Indonesia Stock Exchange for the 2019-2021 period. The type of data used in this study is secondary data in the form of company financial reports which are used as samples. The research method used in this study is a quantitative research method. The sample was selected using the purposive sampling method. To test the hypothesis, this research uses multiple linear regression analysis. Based on the results of this study, it shows that prudence has an effect on the integrated report, Audit tenure does not have an effect on the audit report, Green Intellectual capital strengthens the effect of Prudence on the integrated report but busy directors do not strengthen the effect of Prudence on the integrated report. Green Intellectual capital strengthens the effect of Audit Tenure on the integrated report but busy directors do not strengthen the effect of Audit Tenure on the integrated report